Study of climatic factors influence on the performance of pneumoshells securing freight during transportation by rail - T. A. Vinokurova; A. B. Galushkin (Вестник Научно-исследовательского института железнодорожного транспорта, 2020)
The article provides the results of a computational study of the influence of external climatic factors (ambient temperature and atmospheric pressure) during the transportation of freights by rail on the performance of the pneumoshell as a means to secure unit and packaged freights in cars and containers. The preservation of the operability of the pneumoshells from the moment of installation to  the moment of removal is determined by the need to maintain an excess pressure inside the pneumoshells not higher than the explosion pressure to prevent destruction of the pneumoshells and not less than zero to prevent its “collapse”. The calculation formulas for the study were obtained according to the Mendeleev — Clapeyron equation. The examples show the dependence of the excess pressure in the pneumoshell on temperature at constant atmospheric pressure for pneumoshells with operating pressures of 0.20, 0.25, 0.30, 0.40, 0.55 and 0.69 bar when the ambient temperature changes from the initial at which the pneumoshell was pumped up to its limit values established by the current regulatory documents and possible when transporting through the territory of Russia. The examples also show the general dependence of the overpressure in the pneumoshell on temperature and atmospheric pressure for pneumoshells with operating pressures of 0.30 and 0.40 bar. Based on the results of computational studies, it is recommended to use pneumoshells with a working pressure of 0.30 bar in cases where freight is not transported by rail from low areas in the high-pressure region with temperatures lower than –30 °C, in these cases — the use of pneumoshells with working pressure of 0.40 bar and above. Taking into account the obtained maximum calculated values of the overpressure inside the pneumoshell, the pressure of the “explosion” of the applied pneumoshell should be at least 0.80 bar.